O crescimento da Igreja Comunidade Cristã Pentecostal em Montes Claros - Simões, Darley Antunes (2011)
This work is a research concerning the phenomenon of pentecostalism and it targets to understand how the growth mecanisms of this religiosity works in the church Comunidade Cristã Pentecostal , known to the date as one of the biggest pentecostal churches in the city of Montes Claros, and one of the most highlightned in the north Minas region. The prominence of this work can be shown through the local social configuration derived from the pentecostal growth, but also, for being a inedited academic work in Montes Claros. As an explanatory hypothesis for the Church growth, we took the thesis developed by Rodney Stark, which enlightened the growth of a region as being dependent on that regions capacity to create and maintain social networks built on the basis of interpersonal links. In front of such hypothesis, we seek to relate the network theory to the context of the church Comunidade Cristã Pentecostal . Therefore, we have performed a fieldwork in which was made a collaborative observation process in the church attendances and other church works, and along with that, we have conducted interviews with the founder pastor of the church, and with participants of such, always relating the contents of this research work with the theory in question. As a result, we have managed to vouch that the growth of Comunidade Cristã Pentecostal is reported mostly to the ability of the church in create and manage the open social networks, nevertheless, it must be added to the capacity of the church to build communal bonds that serve as an environmental element to the spread of social networks